2021
DOI: 10.3390/socsci10120472
|View full text |Cite
|
Sign up to set email alerts
|

A Review of First-Year Student Stress and Social Support

Abstract: The present paper reviews empirical literature on stress and social support relative to first-year post-secondary students, published between 1996 and 2020. Empirical studies included in the literature search focused on stress, coping, and social support specifically among first-year undergraduate students while studying in countries adopting North American higher education models comparable to the United States and Canada. This review examines contextual and psychological antecedents and correlates of stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…The literature also suggests university students feel a higher level of stress in comparison to their friends and family who do not attend university (Nerdrum et al, 2006). Stress can manifest as anxiety and depression (Maymon and Hall, 2021), and rates of psychological distress in students have been shown to at least equal (Macaskill, 2013), if not surpass those in the general population (Khawaja and Dempsey, 2008;Browne et al, 2017). Unsurprisingly, researchers have determined negative relationships between student stress and wellbeing (Pascoe et al, 2020), stress and academic performance (Pluut et al, 2015) and wellbeing and dropout rates in higher education (HE) (Mistler et al, 2012), and have identified a connection between attrition rates and levels of support offered to students (Ricks et al, 2014;Cherastidtham and Norton, 2018), Many stressors have the potential to tax student coping.…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature also suggests university students feel a higher level of stress in comparison to their friends and family who do not attend university (Nerdrum et al, 2006). Stress can manifest as anxiety and depression (Maymon and Hall, 2021), and rates of psychological distress in students have been shown to at least equal (Macaskill, 2013), if not surpass those in the general population (Khawaja and Dempsey, 2008;Browne et al, 2017). Unsurprisingly, researchers have determined negative relationships between student stress and wellbeing (Pascoe et al, 2020), stress and academic performance (Pluut et al, 2015) and wellbeing and dropout rates in higher education (HE) (Mistler et al, 2012), and have identified a connection between attrition rates and levels of support offered to students (Ricks et al, 2014;Cherastidtham and Norton, 2018), Many stressors have the potential to tax student coping.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Unsurprisingly, researchers have determined negative relationships between student stress and wellbeing (Pascoe et al, 2020), stress and academic performance (Pluut et al, 2015) and wellbeing and dropout rates in higher education (HE) (Mistler et al, 2012), and have identified a connection between attrition rates and levels of support offered to students (Ricks et al, 2014;Cherastidtham and Norton, 2018), Many stressors have the potential to tax student coping. A major finding is that the first year of university is the most difficult for students to adjust to Garett et al (2017) and Maymon and Hall (2021). These students are focused on the change in their environment including new relationships, managing finances and possibly moving away from the family home, as well as encountering the developmental challenges that arise as they enter young adulthood.…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 3 more Smart Citations